Bridging the Gap between Technology and Languages. (2015) - Bordas, Virginia-Maria
Abstract: The success of technology breakthroughs, innovation and knowledge transfer depends on a better communication and visibility. And language competencies are more and more important. Engineers and engineering graduates can develop the skills needed to perform various activities such as: technical communication, technical writing, technical translations, terminologist or subject matter experts. This article will develop the types of activities and the skills needed to be developed to become a language expert as well to support technology and knowledge dissemination at a global level, for various markets.